An economic evaluation of an intervention to increase demand for medical male circumcision among men aged 25-49 years in South Africa - M. Holmes; R. Mukora; D. Mudzengi; S. Charalambous; C. M. Chetty-Makkan; H. Kisbey-Green; M. Maraisane; J. Grund (BMC, 2021)
Abstract Background Studies estimate that circumcising men between the ages of 20-30 years who have exhibited previous risky sexual behaviour could reduce overall HIV prevalence. Demand creation strategies for medical male circumcision (MMC) targeting men in this age group may significantly impact these prevalence rates. Objectives The objective of this study is to evaluate the cost-effectiveness and cost-benefit of an implementation science, pre-post study designed to increase the uptake of male circumcision for ages 25-49 at a fixed MMC clinic located in Gauteng Province, South Africa. Methods A health care provider perspective was utilised to collect all costs. Costs were compared between the standard care scenario of routine outreach strategies and a full intervention strategy. Cost-effectiveness was measured as cost per mature man enrolled and cost per mature man circumcised. A cost-benefit analysis was employed by using the Bernoulli model to estimate the cases of HIV averted due to medical male circumcision (MMC), and subsequently translated to averted medical costs. Results In the 2015 intervention, the cost of the intervention was $9445 for 722 men. The total HIV treatment costs averted due to the intervention were $542,491 from a public care model and $378,073 from a private care model. The benefit-cost ratio was 57.44 for the public care model and 40.03 for the private care model. The net savings of the intervention were $533,046 or $368,628 - depending on treatment in a public or private setting. Conclusions The intervention was cost-effective compared to similar MMC demand interventions and led to statistically significant cost savings per individual enrolled.